Exploring the Perspectives of Older People on the Concept of Home - Deborah Hatcher; Esther Chang; Virginia Schmied; Sandra Garrido (Journal of Aging Research)
Objectives. Continuing to live at home is arguably one of the most important challenges older persons face as they age. The aim of this study was to clarify how older adults conceptualise home through age-related lifestyle changes. Methods. Principles from grounded theory were used to examine the perspectives of 21 older adults obtained from three focus group discussions and 10 in-depth semistructured interviews. Results. Four major categories were developed: “anchoring self,” “enabling freedom,” “being comfortable,” and “staying in touch.” Discussion. For the participants in this study remaining at home enabled a sense of independence and freedom, self-worth and identity, comfort, and an ongoing active role in the community. However, some aspects of home could be renegotiated despite changes to living location, with new social connections able to be forged and personal comforts being transferrable. This holds important implications for supporting older persons to both sustain living at home and to adjust to changing circumstances, suggesting the importance of drawing on the experiences of older persons themselves in developing strategies to promote successful aging.